Transcriptome Analysis of the Accumulation of Astaxanthin in Haematococcus pluvialis Treated with White and Blue Lights as well as Salicylic Acid. (14th July 2022) - Wei, Zuoxi; Sun, Fengjie; Meng, Chunxiao; Xing, Wei; Zhu, Xiangyu; Wang, Chang; Cao, Kai; Zhang, Chengsong; Zhu, Bingkui; Yao, Ting; Gao, Zhengquan
Abstract : Haematococcus pluvialis is the most commercially valuable microalga for the production of natural astaxanthin, showing enhanced production of astaxanthin with the treatments of high-intensity light and hormones. The molecular mechanisms regulating the biosynthesis of astaxanthin in H . pluvialis treated with white light, blue light, and blue light with salicylic acid (SA) were investigated based on the transcriptome analysis. Results showed that the combined treatment with both blue light and SA generated the highest production of astaxanthin. A total of 109, 443 unigenes were identified to show that the genes involved in the tricarboxylic acid (TCA) cycle, the pentose phosphate pathway (PPP), and the astaxanthin biosynthesis were significantly upregulated to increase the production of the substrates for the synthesis of astaxanthin, i.e., pyruvate and glyceraldehyde-3-phosphate generated in the TCA cycle and PPP, respectively. Results of transcriptome analysis were further verified by the quantitative real-time PCR (qRT-PCR) analysis, showing that the highest content of astaxanthin was obtained with the expression of the bkt gene significantly increased. Our study provided the novel insights into the molecular mechanisms regulating the synthesis of astaxanthin and an innovative strategy combining the exogenous hormone and physical stress to increase the commercial production of astaxanthin by H . pluvialis .